The Peloponnesian War - Kagan, Donald (Penguin Books, 2004)
For three decades in the fifth century b.c. the ancient world was torn apart by a conflict that was as dramatic, divisive, and destructive as the world wars of the twentieth century: The Peloponnesian War. Donald Kagan, one of the world's most respected classical, political, and military historians, here presents a new account of this vicious war of Greek against Greek, Athenian against Spartan. The Peloponnesian War is a magisterial work of history written for general readers, offering a fresh examination of a pivotal moment in Western civilization. With a lively, readable narrative that conveys a richly detailed portrait of a vanished world while honoring its timeless relevance. The Peloponnesian War is a chronicle of the rise and fall of a great empire and of a dark time whose lessons still resonate today. One of the world's foremost historians presents a fresh look at the greatest war of ancient Greece and a pivotal moment in Western civilization that still resonates today.